CONSIDERATIONS ON THE CLIMATE CHARACTERIZATION OF THE AGRICULTURAL YEAR 2011 – 2012 FOR THE MAIZE CROP IN THE CENTRAL BĂRĂGAN PLAIN - Dana Maria (OPREA) CONSTANTIN; Elena BOGAN; Elena GRIGORE; Marina Aurelia ANTONESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The maize is a culture of strategic importance for a country’s agriculture. The productivity of the maize crop has significant fluctuations from year to year because of the climate variability, but mostly because of the occurrence of extreme weather events. The aim of this paper is to analyze and correlate the agro-climatic resources with the agrocultural production from the agricultural year 2011 – 2012, in the context of the present and predicted climate changes. The study area is the Central Bărăgan Plain. This area is located in a zone where dryness and drought phenomena are produced and are growing in frequency from the West and South-West to the East and North-East, in accordance with the degree of dryness. Taking into account the precipitation amounts, the agricultural year 2011 – 2012 was a year with a dry pluviometric regime. Therefore, the vegetation stage of the maize crop was medium and weak, in general, resulting an average maize production per hectare lower than in the previous years. Knowing the climate conditions and their impact on the main components of an agricultural system, of the level of yields and quality of the crops provides the possibility to reduce losses by respecting the adequate agricultural technologies.